2000
DOI: 10.1128/jvi.74.20.9553-9561.2000
|View full text |Cite
|
Sign up to set email alerts
|

Passage of Classical Swine Fever Virus in Cultured Swine Kidney Cells Selects Virus Variants That Bind to Heparan Sulfate due to a Single Amino Acid Change in Envelope Protein E rns

Abstract: Infection of cells with Classical swine fever virus (CSFV) is mediated by the interaction of envelope glycoprotein Erns and E2 with the cell surface. In this report we studied the role of the cell surface glycoaminoglycans (GAGs), chondroitin sulfates A, B, and C (CS-A, -B, and -C), and heparan sulfate (HS) in the initial binding of CSFV strain Brescia to cells. Removal of HS from the surface of swine kidney cells (SK6) by heparinase I treatment almost completely abolished infection of these cells with virus t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
136
0
1

Year Published

2001
2001
2011
2011

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 124 publications
(142 citation statements)
references
References 47 publications
(57 reference statements)
5
136
0
1
Order By: Relevance
“…The binding of CSFV strain Brescia (9, 10) and BVDV strain PE515 (12) was demonstrated for GAGs, e.g., heparin or heparan sulfate (9). Glycoprotein E rns was identified as a primary ligand.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The binding of CSFV strain Brescia (9, 10) and BVDV strain PE515 (12) was demonstrated for GAGs, e.g., heparin or heparan sulfate (9). Glycoprotein E rns was identified as a primary ligand.…”
Section: Discussionmentioning
confidence: 99%
“…In either case, a single point mutation (CSFV: Ser 476 Arg) in E rns was the reason for the high affinity for GAGs. Very likely this point mutation is a result of tissue culture adaptation of the particular virus isolates (9,10,12), but GAGs also may serve with a low affinity as alternative receptors. An alternative receptor(s) may account for the residual susceptibility (Ϸ1%) of MDBK cells to BVDV NADL, since its entry was not inhibited even by high concentrations of anti-CD46 bov antibodies (data not shown).…”
Section: Discussionmentioning
confidence: 99%
“…A correlation between plaque size in vitro and pathogenesis in vivo has yet to be established. Hulst et al (11,12) serially passaged CSFV Brescia in SK6 cells to generate heparan sulfate binding-dependent small-plaque variants that contained mutations in the E rns protein; however, these varients had an unaltered virulence phenotype in pigs (11,12).…”
Section: Discussionmentioning
confidence: 99%
“…Thus, HS is considered as an initial receptor for a number of viruses (Compton et al, 1993;Mettenleiter et al, 1990;Okazaki et al, 1991;WuDunn & Spear, 1989;Zhu et al, 1995). While many enveloped viruses have been associated with HS binding (Asagoe et al, 1997;Bernard et al, 2000;Byrnes & Griffin, 1998;Chung et al, 1998;Hulst et al, 2000Hulst et al, , 2001Jusa et al, 1997;Krusat & Streckert, 1997;Mondor et al, 1998;Summerford & Samulski, 1998), the number of non-enveloped viruses reported to use HS for attachment to the host cell is limited. Among the Picornaviridae family, it has been shown that foot-and-mouth disease virus (FMDV) binds to HS, although it reflects an adaptation to in vitro cultures (Fry et al, 1999;Jackson et al, 1996;Sa-Carvalho et al, 1997).…”
Section: Introductionmentioning
confidence: 99%